Myocardial Damage Patterns in Patients with Left Ventricular Systolic Dysfunction with and Without Coronary Artery Disease Referred for Cardiac Magnetic Resonance - Justyna M. Sokolska; Katarzyna Logoń; Magdalena Pszczołowska; Wojciech Kosmala (Biomedicines, 2025)
Background: Cardiac magnetic resonance (CMR) is widely used to determine the underlying cause of left ventricular (LV) systolic dysfunction. Patients with ischemic disease are less frequently referred for CMR, as the underlying disease is often presumed to explain LV systolic dysfunction. However, various etiologies of myocardial impairment may coexist. Late gadolinium enhancement (LGE) is a technique used for tissue characterization, particularly visualization of myocardial fibrosis. Objectives: The aim of this study was to assess the prevalence of LGE patterns suggesting ischemic or non-ischemic etiology of myocardial damage in patients with LV systolic dysfunction with and without known coronary artery disease (CAD). Methods: 131 patients (76% male, 55 ± 15 years old) with LV ejection fraction (LVEF) ≤ 50% in echocardiography underwent CMR between December 2021 and November 2022. Patients were divided according to the known history of CAD. Regional subendocardial and transmural LGE was interpreted as ischemic etiology, whereas midmyocardial and subepicardial LGE was non-ischemic. Results: The mean LVEF assessed in CMR was 35 ± 10%. A total of 122 patients underwent CMR with LGE sequence. LGE was detected in 62% of patients: 34% had a non-ischemic pattern, 16% ischemic, and 11% mixed. LGE patterns did not differ between patients with and without CAD. In every third patient with CAD and almost every second patient without CAD, no myocardial fibrosis was detected. A completely normal CMR study was found in 6% of patients without CAD and 1% of patients with CAD (all p NS). Conclusions: The LGE patterns suggesting ischemic or non-ischemic myocardial damage are similarly prevalent in patients with and without known CAD. The diagnosis based solely on clinical information may be unreliable, as LV dysfunction might have multifactorial origins. The absence of local myocardial fibrosis is relatively common in patients with LV dysfunction, irrespective of its etiology.